Five‐day stability of thawed plasma: solvent/detergent‐treated plasma comparable with fresh‐frozen plasma and plasma frozen within 24 hours. Issue 2 (29th September 2015) - Neisser‐Svae, Andrea; Trawnicek, Laurenz; Heger, Andrea; Mehta, Trupti; Triulzi, Darrell
Abstract : BACKGROUND: Plasma stored refrigerated for up to 5 days after thawing is common practice in many US hospitals. Therefore, clotting factor activities in fresh‐frozen plasma (FFP), plasma frozen within 24 hours (PF24), and solvent/detergent‐treated plasma (SDP), thawed and stored at 1 to 6°C for up to 5 days, were investigated. STUDY DESIGN AND METHODS: Five A, B, O, and AB units of FFP, PF24, and SDP were thawed and maintained for 5 days at 1 to 6°C. The activity of factor (F)V, FVII, FVIII, protein S (PS), and ADAMTS13 was determined in each unit at baseline and every 24 hours thereafter for 5 days. RESULTS: After thaw, mean values of the variables tested were within the normal range in all three plasma products although, in SDP, FVIII activity was significantly lower (p = 0.0039). After 5 days of storage all factors significantly declined except for ADAMTS13 activity, which was stable. Mean FVIII and ADAMTS13 activity was comparable in all three plasma products and within the normal range, mean FV activity was significantly lower in FFP and PF24 (p<0.0001) compared to SDP, and mean FVII activity was significantly lower in PF24 (p<0.03) than in FFP or SDP. Mean PS activity was below the normal range in all three plasma products with the lowest values in SDP (p = 0.0001). CONCLUSION: Over 5 days of refrigerated storage the changes in the measured coagulation factors in FFP, PF24, and SDP are comparable. Clinical follow‐up is needed to assess whether slightly lower PS levels in SDP are clinically important.